Proceedings of the Ocean Drilling Program, 157 Scientific Results 1998
DOI: 10.2973/odp.proc.sr.157.147.1998
|View full text |Cite
|
Sign up to set email alerts
|

Calcareous nannofossil biostratigraphy and sediment accumulation of turbidite sequences on the Madeira Abyssal Plain, Sites 950-952

Abstract: Drilling on the Madeira Abyssal Plain during Leg 157 penetrated deep into the sequence of interbedded turbidites and pelagic sediments that underlie the plain. The turbidites generally have abundant and well-preserved calcareous nannofossil assemblages, with the interbedded pelagic sediments having variable preservation and abundance of nannofossils dependent on CaCO 3 content. Poor preservation in pelagic sediments from the Paleogene and Miocene necessitated the use of nannofossil datums from turbidites to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…To further aid age verification of the turbidites recovered in the piston cores, previous biostratigraphic and magnetostratigraphic dates from ODP studies are utilized. A R. asanoi biostratigraphic event at 36.51–37.52 m depth at ODP Site 950, 5 cm above bed Mz, is dated at 830 ka [ Howe and Sblendorio‐Levy , ]. The top of the Jaramillo event (980 ka) occurs at 39.7 m core depth below bed Mz and above bed Mab at ODP Site 950.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further aid age verification of the turbidites recovered in the piston cores, previous biostratigraphic and magnetostratigraphic dates from ODP studies are utilized. A R. asanoi biostratigraphic event at 36.51–37.52 m depth at ODP Site 950, 5 cm above bed Mz, is dated at 830 ka [ Howe and Sblendorio‐Levy , ]. The top of the Jaramillo event (980 ka) occurs at 39.7 m core depth below bed Mz and above bed Mab at ODP Site 950.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the FO of G. ericsonii is at ∼0.38 Ma, with the LO at 0.015 Ma [ Biekart , 1989]. The coccolith biostratigraphy used to date the ODP record is published and documented by Howe and Sblendorio‐Levy [].…”
Section: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Weaver [1994] showed that each individual turbidite contains a relatively narrow age range of sediment, typically 0.5 million years or less. Thus useful stratigraphic information can be obtained from the turbidites in the absence of data from the pelagic layers [ Howe and Sblendorio‐Levy , 1998].…”
Section: Abyssal Plain Sequence and Sediment Sourcesmentioning
confidence: 99%